PENGUASAAN RANGKAIAN TES KEBUGARAN JASMANI INDONESIA (TKJI) MELALUI DISKUSI DAN SIMULASI (Kajian Pustaka Pemahaman Teori dan Praktek TKJI Terhadap Mahasiswa PGSD UMTAS) - Permana, Rahmat (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
Elementary School teachers at primary school level are groomed to become classroomteachers in science subjects, social studies, Indonesian Language, Civic Education andmathematics. While the position is beyond the fifth lesson Physical Education such subjects, butfield data show that some elementary school gym teacher shortage this have an impact onclassroom teachers forced to teaching phsical Education. If this happens then certainly the goal oflearning the sport in elementary school will not be achieved. The writer tries to optimize the abilityof students elementary teacher education on a series of physical fitness tests Indonesia. Becausethese tests are the basis for a sports teacher to determine the level of physical fitness in children.By knowing these tests students are expected to teach at the elementary level sport elementaryschool age children if the situation in the school is no physical eduction teacher. The series of testsconsisting of 1. Running 30 meters, 2. Pull Up, 3. Sit Up, 4. Skip Upright, 5. Running 600 meters.The fifth series of tests has had a physical fitness test norm Indonesia that has been set by theexperts of physical education, the author only do in-depth understanding to the students throughthe study of five discussion meetings and perform simulation test as much as two meetings.